MMP9 is protective against lethal inflammatory mass lesions in the mouse colon - Andreas Hald; Birgitte Rønø; Maria C. Melander; Ming Ding; Susanne Holck; Leif R. Lund (The Company of Biologists, 2011)
SUMMARY The family of matrix metalloproteinases (MMPs) is responsible for extracellular matrix degradation during physiological and pathophysiological tissue remodeling processes such as embryogenesis, tissue repair and cancer progression. Despite these important roles of MMPs, inhibition or ablation of individual members of the MMP family in animal models have been shown to have little effect. It has been speculated that this results from a functional overlap between individual MMPs and (as-yet-unclassified) functional overlaps between MMPs and other protease systems. We here present genetic data showing that concomitant ablation of MMP9 (gelatinase B) and the serine protease plasmin results in lethal inflammatory mass lesions in the colon. These lesions possessed several histological attributes that are characteristic of mucosal prolapse seen in humans, and they were found to be associated with splenomegaly, enlarged mesenteric lymph nodes, decreased thymus size and altered populations of circulating immune cells. A time-course study provided evidence that the massive lymphoid hyperplasia and reactive changes were secondary to discrete fibrinous lesions also observed in mice only deficient for plasminogen (Plg), the zymogen for plasmin. These data demonstrate a non-appreciated vital protective role for MMP9 in the absence of Plg.